Extractive Spectrophotometric Determination of Palladium(II) Using 2-Hydroxy-1-naphthalenecarboxaldehyde Hydrazine Carboxamide as an Analytical Reagent - LOKHANDE, R.S.; SAINI, NAMRATA (Asian Journal of Chemistry, 2010)
A spectrophotometric method has been developed for the determination of Pd(II) using 2-hydroxy-l-naphthalene carboxaldehyde hydrazine carboxamide as an analytical reagent. The reagent forms an orange-coloured complex with Pd(ll), which can be quantitatively extracted into ethyl acetate at pH 4.2 having absorption maxima at 410 nm. Beer's law is obeyed over the range of 0.55 g/mL to 2.50 μg/mL of palladium. The molar absorptivity is 0.4 x 103 L mol-1 cm-1 and Sandell's sensitivity is 1.50 x 10-5 μg cm-2. The stoichiometric ratio of the complex was found to be 1 : 2. The proposed method has been applied to determine palladium in silver alloy, palladium complexes and palladium catalysts.